Nature in common? : environmental ethics and the contested foundations of environmental policy - Minteer, Ben A., 1969- (Philadelphia : Temple University Press, 2009)
A groundbreaking contribution to a central debate in environmentalism.
Unity among environmentalists? Debating the values-policy link in environmental ethics / Ben A. Minteer -- Contextualism and Norton's convergence hypothesis / Brian K. Steverson -- Convergence and contextualism: some clarifications and a reply to Steverson / Bryan G. Norton -- Why Norton's approach is insufficient for environmental ethics / Laura Westra -- Convergence in environmental values: an empirical and conceptual defense / Ben A. Minteer and Robert E. Manning -- The relevance of environmental ethical theories for policy making / Mikael Stenmark -- Converging versus reconstituting environmental ethics / Holmes Rolston III -- Environmental ethics and future generations / Douglas Maclean -- The convergence hypothesis falsified: implicit intrinsic value, operational rights, and de facto standing in the endangered species act / J. Baird Callicott -- Convergence in an agrarian key / Paul B. Thompson -- Convergence and ecological restoration: a counterexample / Eric Katz -- Does a public environmental philosophy need convergence hypothesis? / Andrew Light -- The importance of creating an applied environmental ethics: lessons learned from climate change / Donald A. Brown -- Who is converging with whom? An open letter to Professor Bryan Norton from a policy wonk / Daniel Sarewitz -- Convergence and divergence: the convergence hypothesis twenty years later / Bryan G. Norton.
Includes bibliographical references (pages 265-297) and index.
Print version record.
JSTOR
Keywords: Human ecology -- Philosophy; Environmentalism -- Philosophy; Environmentalism -- Moral and ethical aspects; Environmental ethics; Écologie humaine -- Philosophie; Environnementalisme -- Philosophie; Environnementalisme -- Aspect moral; Éthique de l'environnement.; PHILOSOPHY -- Ethics & Moral Philosophy; PHILOSOPHY -- General; Environmental ethics; Environmentalism -- Philosophy; Human ecology -- Philosophy; Umweltethik; Aufsatzsammlung